EFEKTIVITAS PENERAPAN SISTEM FAKTUR PAJAK ELEKTRONIK SEBAGAI UPAYA PENCEGAHAN FAKTUR PAJAK FIKTIF: PERSPEKTIF REGULATOR - Permana, Andika Galih; Wijayanti, Nanda Ayu (Faculty of Economics and Business University of Mataram, 2023)
The government has required the implementation of an electronic tax invoice system to prevent tax fraud, especially fictitious tax invoices, with the issuance of PER-16/PJ/2014. However, after the implementation of the electronic tax invoice system, there are still cases of fictitious tax invoices. The purpose of this study is to evaluate the effectiveness of electronic tax invoices in preventing fictitious tax invoices from the perspective of the Directorate General of Taxes (DJP). The research methodology used is a case study using a qualitative descriptive approach. The effectiveness of the e-Faktur system in preventing fictitious tax invoices was evaluated based on Delone & Mclean’s IS Success Model and Fraud Prevention Theory. The findings show that the implementation of the electronic tax invoice system has not been effective in preventing fictitious tax invoices. The implementation of electronic tax invoices has not optimally stopped fictitious tax invoice cases because it has not succeeded in identifying manipulative transactions, thus creating opportunities for perpetrators to issue fictitious tax invoices. This research can be used as a consideration for the DJP to improve the performance of the electronic tax invoice system in preventing fictitious tax invoices.